Complex coacervation between flaxseed protein isolate and flaxseed gum. (June 2015) - Kaushik, Pratibha; Dowling, Kim; Barrow, Colin J.; Adhikari, Benu
Abstract: Flaxseed protein isolate (FPI) and flaxseed gum (FG) were extracted, and the electrostatic complexation between these two biopolymers was studied as a function of pH and FPI-to-FG ratio using turbidimetric and electrophoretic mobility (zeta potential) tests. The zeta potential values of FPI, FG, and their mixtures at the FPI-to-FG ratios of 1:1, 3:1, 5:1, 10:1, 15:1 were measured over a pH range 8.0–1.5. The alteration of the secondary structure of FPI as a function of pH was studied using circular dichroism. The proportion of ɑ-helical structure decreased, whereas both β-sheet structure and random coil structure increased with the lowering of pH from 8.0 to 3.0. The acidic pH affected the secondary structure of FPI and the unfolding of helix conformation facilitated the complexation of FPI with FG. The optimum FPI-to-FG ratio for complex coacervation was found to be 3:1. The critical pH values associated with the formation of soluble (pHc) and insoluble (pHɸ1 ) complexes at the optimum FPI-to-FG ratio were found to be 6.0 and 4.5, respectively. The optimum pH (pHopt ) for the optimum complex coacervation was 3.1. The instability and dissolution of FPI–FG complex coacervates started (pHɸ2 ) at pH 2.1. These findings contribute to the development of FPI–FG complex coacervates as delivery vehicles for unstable albeit valuable nutrients such as omega-3 fatty acids. Highlights: Flaxseed protein and gum were extracted from raw flaxseed. Interactions of protein and polysaccharide were studied as function of pH and different mixing ratios. Different phase boundaries related to structure-forming events were determined. Changes in the secondary structure of protein with lowering of pH were found facilitating the interactions of protein and polysaccharide. Optimum pH and protein-to-polysaccharide ratio for complexation was found to be 3.1 and 3:1.